ANALISIS KINERJA PAMONG DESA DALAM MELAKUKAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA BEDAGUNG KECAMATAN PANEKAN KABUPATEN MAGETAN - Chairil Anwar (JISOS: JURNAL ILMU SOSIAL, 2022)
Analysis of Performance Employee to do take up of Land and Building Tax in Bedagung Village, Panekan District, Magetan Regency, Accounting Study Program, Faculty of Economics, Nahdlatul Ulama University, Sidoarjo. This research aims to knowing how to performance employee to do take up of land and building tax in Bedagung Village, Panekan District, Magetan Regency. Researchers use descriptive qualitative, performance of to do take up of land and building tax right regulations and legal basis be regulated in Magetan Regency. The performance village apparatus to do take up of land and building tax in BedagungVillage very good. And Bedagung Village always got appreciation Panekan Districtextent about fastest payment. All of these support from headman and villageadministration take effect of performance. And quality of performance employee in knowledge very good